MINERAL NUTRITION IN THE TREE Calophyllum brasiliense Cambess. (Calophyllaceae)1 - Morandi,Paulo Sérgio (2017)
ABSTRACT Riparian and gallery forests located at the “arc of deforestation” have been undergoing fast degradation. With the implementation of the new Brazilian Forest Code (Law 12,651 of 2012), these can be reduced further. Thus, new studies on seedling production for ecological restoration should be carried out using native species from the Amazon and Cerrado. The objective of the present study was to assess under which shading levels the seedlings of Calophyllum brasiliense, a tree species typical of humid environments, show the highest values of growth and nutrient use efficiency, aiming at using these seedlings for restoration. The study was carried out in a plant nursery of the State University of Mato Grosso in Nova Xavantina, Brazil. We assessed seedling growth in diameter, height, number of leaves, production of shoot and root dry mass, Dickson quality index (DQI), and efficiency in the internal use of nutrients (EIUN) in greenhouses at 0 (full sunlight), 30, 50, 70, and 90% shading. The treatments at 50 and 70% shading showed the best results. Ecologically, the species responds well under both gap conditions (50% shading) and canopy or closing gap conditions (70% shading). Our results showed that the ideal conditions to produce seedlings of this species with high EIUN are obtained in greenhouses with 70% shading.